The relationship between self mutilative behavior, suicide attempt history and impulsivity and some clinical variables in male opiate-dependent patients - Baykara, Sema; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Objective: The aim of this study is to investigate the relationship between self-mutilative behavior (SMB), suicide attempt history (SAH) and impulsivity which is known to play an important role in the etiology, duration, course of treatment, and relapse of addiction in male patients with opiate use disorder. Methods: Ninety five inpatient people diagnosed with opiate use disorder were included in the study. There were three groups according to their clinical findings: Group 1 included the patients with SMB and SAH, Group 2 included the patients with only SMB and Group 3 included the patients showing none of these behaviors. The Sociodemographic Form, Barratt Impulsivity Scale-11 (BIS-11), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were administered. Results: In terms of age there was a significant difference between the Group 1 and Group 3, to be lower in Group 1. There was a significant difference between Group 1 and Group 3 in terms of job status to be higher in Group 3. There was a significant difference between Group 1 and Group 2 and 3 in terms of childhood abuse history. There was a significant difference between Group 1 and Group 3, and between Group 1 and Group 2 to be higher in Group 1 In terms of BDI and BAI scores. There was a significant difference between Group 3 and Group 1 in terms of BIS-11 motor and motor impulsivity subscores to be higher in Group 1; thus there was no difference between Group 2 and Group 1 and 3. There was a significant difference between Group 1 and Group 2 to be higher in Group 1 in terms of self-control. There were no differences in terms of age, job status, childhood abuse history, BDI, BAI and BIS-11 scores between Group 2 and Group 3. Conclusion: Suicide attempt and SMB include impulsivity in etiology, make treatment difficult and is effective on relapse. However, psychotherapeutic approaches considering that SMB alone is not associated with significant impulsivity and increased depression and anxiety, and that the association of SAH and SMB is associated with increased impulsivity and increased anxiety and depression, may improve treatment success in opiate use disorder.
Erkek opiyat kullanım bozukluğu hastalarında kendine zarar verici davranış ve intihar girişimi öyküsünün dürtüsellik ve bazı klinik verilerle ilişkisi
Keywords: heroin dependence; self mutilation; suicide; attempted; defense mechanisms